Temporomandibular disorder-associated risk factors - Elizabeth de la Torre Rodríguez; Iris Aguirre Espinosa; Viena Fuentes Mendoza; Pedro Angel Peñón Vivas; Desiderio Espinosa Quirós; Jackeline Núñez Fernández (Editorial Ciencias Médicas, 2014)
Introduction: temporomandibular disorders comprise a group of musculoskeletal conditions that affect temporomandibylar joint, masticatory muscles and adjacent anatomical structures, complex and shaped by several interacting risk factors. Knowledge of these disorders is of great value so that one can act upon them and prevent the occurrence and/or aggravation of disease. Objective: to characterize the study population according to sociodemographic variables such as age, sex, precipitating factors, parafunctional habits and occlusal disorders. Methods: a cross-sectional, observational and descriptive study was conducted in «Miguel Enriquez» clinical and surgical university hospital. The study population was made up of 181 patients who went to the multidisciplinary service of integrated care to the temporomandibular joint in the period of January 2010 through January 2012. Results: of the total number of patients, 133 were females for 73 %. The 25-35 years age group was represented by 45 patients for 24 %. Bruxism was seen in 79 %, lingual interposition in 24 % of cases whereas 52 % presented with non-replaced absent teeth. Conclusions: females prevailed and the most represented age group was 25-35. The most observed predisposing factor was absent teeth which were not replaced by dentures. The prevailing precipitant factor was bruxism and no perpetuating factors of temporomandibular disorder were unobserved.   Keywords: temporomandibular disorders, risk factors, temporomandibular joint.